The enduring link between demography and inflation - Mikael Juselius; Előd Takáts (Bank of Finland, 2018)
Demographic shifts, such as population ageing, have been suggested as possible explanations for the recent decade-long spell of low inflation. We identify age structure effects on inflation from cross-country variation in a panel of 22 countries from 1870 to 2016 that includes standard monetary factors. We document a robust relationship that is in line with the lifecycle hypothesis: a larger share of dependent population is inflationary, whereas a larger share of working age population is disinflationary. This relationship accounts for the bulk of trend inflation, for instance, about 7 percentage points of US disinflation since the 1980s. It predicts rising inflation over the coming decades.
URN:NBN:fi:bof-201804091430
Keywords: E31; E52; J11; 330